การวิจัยประเมินความต้องการจำเป็นเพื่อพัฒนาความเป็นชุมชนแห่งการเรียนรู้ทางวิชาชีพของครูโรงเรียนราชวินิต มัธยมสังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 1 - เลิศพฤกษ์พนา, มาลิสา; กุโลภาส, ธีรภัทร (An Online Journal of Education, 2018)
The objectives of this research paper are: 1)to study the present situation and expected situation for developing PLC of RajavinitMathayom School's teachers. 2) A needs assessment research study for developing PLC of the School's teachers. The sampling group of this research composed of 13 people: The school's director, 4 assistant directors, and 8 heads of learning areas. The research tools that the researcher used are questionnaires, and the forums. The data was analyzed by applying thefrequency, percentage, standard deviation, and PNIModifientechnique. That the findings are as follow: there are five elements of conceptual framework involving with PLC :1) defining and sharing vision, core values, mission, and objectives together. 2) co-learningand uniting 3) being responsible for group's objective about students' learning 4) reflecting the work performance in order to increase professional development 5) joint leadership and administration for supporting professional development. After analyzing each category, the researcher finds that, in general, the average of the present situation of RajavinitMathayom School's PLC is in the medium level.The index value of needs of PLC development is 0.406. The category, which can be proved to find the most value needs is reflecting the work performance for PLC development PNIModifien=0.543, and the category be ranked in the second position in joint leadership and administration for supporting the development of PLC